Increased Trypanosoma brucei cathepsin-L activity inhibits human serum-mediated trypanolysis - Sam Alsford (Microbial Cell)
Most African trypanosomes, including the veterinary species Trypanosoma brucei brucei and T. congolense are susceptible to lysis by human serum. A recent study by Alsford et al. [PLoS Pathogens (2014) 10, e1004130] has identified a T. b. brucei lysosomal cathepsin with an inhibitory effect on human serum’s trypanolytic action.